Letters of St. Athanasius (Sakharov) from the Archive of Hieromartyr Seraphim (Samoilovich) - Kosik Ol'ga (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The publication is devoted to the unknown letters of Holy Confessor Athanasius (Sakharov), the Bishop of Kovrov, to the Holy Martyr Metropolitan Kirill (Smirnov) and St. monk-martyr archimandrite Neophyte (Osipov), who were called by friends as «Abba». In the letter to Metropolitan Kirill (Smirnov) St. Athanasius has literally outlined the content of his unknown letter to the Deputy of the Patriarchal Locum Tenens, Metropolitan Sergius (Stragorodsky). In this letter the Bishop says about the reasons for his departure relating to the abuse of power that was permitted by Locum Tenens Peter (Polyansky) to Metropolitan Sergius. The relationship between Bishop Athanasius and the closest in spirit to him Church leaders was shown in the letters: Metropolitan Kirill (Smirnov) and Archimandrite Neophytos (Osipov). The letters covers also the circumstances of his exiles, wanderings and the conﬂict situation because of the Athanasius’s renouncement to serve in the Vladimir diocese.